Thematic analysis on novice learner"™s procedural writing challenges: Insights, influences, and implications - Ristati, Ristati; Bahing, Bahing; Sujiyani, Erma; Susanty, Susanty; Norahmi, Maida; Nugraha, Richard Ferry; Amalia, Novika (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
This research article provides an examination of the challenges faced by students during the composition of procedure texts. It aims to uncover factors influencing students' proficiency. Utilizing thematic analysis, we analyzed students' written texts and conducted interviews with junior high school English teachers and students, providing a holistic perspective.   Four significant areas of difficulty were identified: minimal word and phrase variations, lack of clarity and precision, ignorance of writing mechanisms, and challenges with grammar and spelling. These challenges provided insights into the recurring patterns of students"™ writing. Factors contributing to these difficulties included motivational factors, language environment, language proficiency, and formal presentation aspects. Student motivation to write and seek comments was hindered by low intrinsic motivation. Students' writing talents were also shaped by language exposure and proficiency, which varied by background and experience. Additionally, formal presentation characteristics and technology-based teaching strategy restrictions underlined the need for improved infrastructure to accommodate various and engaging teaching methods. In conclusion, the research sheds light on the intricate landscape of students' struggles in composing texts and underscores the urgency of providing tailored teaching strategies to address these challenges effectively while also keeping the influencing factors in consideration.